STUDI PERSEPSI DAN PREFERENSI PENGHUNI TERHADAP RUANG HIJAU DI RUMAH SUSUN SEDERHANA SEWA PROVINSI DKI JAKARTA SERTA STRATEGI PERBAIKANNYA - Nenah Suminah; Bambang Sulistyantara; Tati Budiarti (Jurnal Lanskap Indonesia, 2017)
The development of Simple flats (Rusunawa) is one of Jakarta municipality’s program in overcoming both high level of urbanization and land limitation issues. Simple flats that dominated by massive multi-storey buildings and pavement areas needs to be balanced by the development of green spaces. The purposes of this study were to analyze resident’s perceptions and preferences of green space and to develop improvement strategies  and design concept to increase resident’s comfort. This study assessed in four Simple flats: Jatirawasari, Tambora, Pulogebang, and Marunda Cluster A.  The methods of this study were  studied responden’s perception and preference by questionaire and SWOT analysis.  The results showed total score perception analysis of green space in four Simple flats in good category.  Matrix mapping based on IFE and EFE SWOT method showed that all four simple flats green space improvement strategy are in the hold and maintain position.  Suggested recommendation in this study were preservation of existing trees, adding new trees and facilities on available spaces on sites.